Efektivitas Penerapan Absensi Face Recognition trrhadap Disiplin Kerja pegawai Dinas Pekerjaan Umum dan Penataan Ruang Kota Palembang - Mareta; Fitriasuri Fitriasuri (J-MSDM (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2025)
This study aims to assess the effectiveness of implementing a facial recognition-based attendance system in improving employee discipline at the Department of Public Works and Spatial Planning (PUPRI of Palembang City. The system has been in use since July 2023, replacing the fingerprint attendance method, which was considered less optimal and prone to manipulation. The research method used is descriptive with a qualitat lue approach, Including direct interulews and analysis of attendance data of Non-PNSD employees during the period from February to April 2025. The findings Indicate that the Implementation of the factal recognition system has had a positive Impact on Improving discipline, as reflected in the decrease in tardiness and unexcused absences Furthermore, interviews with several employees revealed that the system operates effectfuely anc also Influences work motluation, as it is directly related to the proulsion of Incentives and performance evaluations. However, there are still challenges, such as delays caused by external factors. Therefore, perlodic evaluations and consistent socialization efforts are necessary to enhance employee compliance with the Implemented attendance system.